2016
DOI: 10.1002/elan.201501112
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Commercial Screen‐printed Electrodes into a Voltammetric Electronic Tongue for the Analysis of Aminothiols

Abstract: A voltammetric sensor array (or electronic tongue) is developed for the simultaneous quantification of cysteine, glutathione and homocysteine without need of previous separation. It is based on the integration of three commercial screen‐printed electrodes (gold curated at high and low temperature and carbon modified with carbon nanotubes). Linear sweep voltammograms measured simultaneously by all three sensors are processed by Partial Least Squares (PLS) regression and different variables selection algorithms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…A preliminary study was made to stablish a convenient working pH for several commercially available screen‐printed electrodes that, according to previous results, could be good candidates to constitute an improved voltammetric electronic tongue. These are the low‐temperature and high‐temperature cured gold electrodes (AuBT and AuAT, respectively) successfully used in , the carbon nanofibers electrode (CNF), a device with similar or even better features than carbon nanotubes , and the simple, cheap and versatile carbon electrode.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A preliminary study was made to stablish a convenient working pH for several commercially available screen‐printed electrodes that, according to previous results, could be good candidates to constitute an improved voltammetric electronic tongue. These are the low‐temperature and high‐temperature cured gold electrodes (AuBT and AuAT, respectively) successfully used in , the carbon nanofibers electrode (CNF), a device with similar or even better features than carbon nanotubes , and the simple, cheap and versatile carbon electrode.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar way, the tests made with different electrodes and analytes suggested that a pH value of 7.4 (obtained with tris buffer) would be a good compromise to obtain an optimal performance of the electrodes when they work together in the same solution. It should be pointed out that, in contrast to the acidic medium used in the previous tongue or the chromatographic method , this optimal pH of 7.4 is really close to biological conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few years, PLS has been described in books and in tutorials [25][26][27][28][29][30][31][32]. Currently, PLS is receiving increased attention in the literature, for instance, during the last year or so, several papers describing the application of PLS to chemical problems have been published [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Pls and Anns For Spectral Interference Correctionmentioning
confidence: 99%